The Pan-Immune-Inflammation Value in microsatellite instability–high metastatic colorectal cancer patients treated with immune checkpoint inhibitors. (June 2021) - Corti, Francesca; Lonardi, Sara; Intini, Rossana; Salati, Massimiliano; Fenocchio, Elisabetta; Belli, Carmen; Borelli, Beatrice; Brambilla, Marta; Prete, Alessandra A.; Quarà, Virginia; Antista, Maria; Fassan, Matteo; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) yielded unprecedented efficacy in patients with microsatellite instability (MSI)–high metastatic colorectal cancer (mCRC). Since the Pan-Immune-Inflammation Value (PIV) is a blood-based biomarker with prognostic usefulness in mCRC, it might predict clinical outcomes and primary resistance to ICIs. Methods: We retrospectively analysed the association of PIV and its early modulation at 3/4 weeks after treatment initiation with the outcomes of MSI-high mCRC patients receiving anti-programmed death-(ligand)1 (PD-[L]1) +/− anti-cytotoxic T-lymphocyte antigen 4 (CTLA-4) agents. PIV was calculated as follows: (neutrophil count × platelet count × monocyte count)/lymphocyte count. PIV cut-offs were determined using the maximally selected rank statistics. Results: A total of 163 patients were included. In the multivariable models for overall survival (OS) and progression-free survival (PFS), both high (>492) baseline PIV (OS: adjusted [a] HR, 3.00; 95% CI, 1.49–6.04, p = 0.002; PFS: aHR, 1.91; 95% CI, 1.06–3.44, p = 0.031) and early PIV increase ≥+30% (OS: aHR, 3.21; 95% CI, 1.65–6.23, p < 0.001; PFS: aHR, 2.25; 95% CI, 1.30–3.89, p = 0.003) confirmed an independent prognostic impact. After stratifying patients according to baseline PIV and ICI regimen, OS and PFS were significantly worse in subjects with high PIV receiving anti-PD-1/PD-L1 monotherapy. Early PIV increase was an independent predictor of clinical benefit (aOR, 0.23; 95% CI, 0.08–0.66; p = 0.007), whereas a trend was observed for baseline PIV (aOR, 0.33; 95% CI, 0.10–1.07; p = 0.065). Conclusion: PIV is a strong predictor of outcomes in MSI-high mCRC patients receiving ICIs. Prospective validation of these results is required to establish its role as a stratification factor for personalised combination strategies. Highlights: PIV is a composite immune-inflammation biomarker with prognostic usefulness in mCRC. High baseline PIV identifies MSI-high mCRC patients with poorer outcomes upon ICIs. Early PIV increase ≥+30% at 3/4 weeks independently correlates with poor OS and PFS. Subjects with high PIV receiving anti-PD-1/PD-L1 monotherapy have worse OS and PFS. Baseline PIV and early PIV variation correlate with primary ICIs resistance.